Strategi Pembelajaran Diferensiasi dalam Pendidikan Inklusif - Suci Febrianti; Damri Damri; Mardhatillah Zulpiani (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2025)
Differentiated instruction has become an essential pedagogical approach in supporting the success of inclusive education, particularly at the elementary school level where students display diverse learning needs, abilities, and characteristics. This article aims to provide a comprehensive analysis of differentiated learning strategies within inclusive classrooms, focusing on the adaptation of content, process, and product to ensure that all students including those with special needs can access and participate meaningfully in the learning process. Using a literature review method based on recent studies related to inclusive education and differentiated instruction, this research highlights that differentiation effectively enhances student engagement, motivation, and learning outcomes through responsive curriculum design, individualized support, and flexible instructional planning. The findings emphasize that the success of differentiated instruction relies heavily on teachers’ pedagogical competence, collaborative practices between classroom teachers and special education teachers, as well as institutional policies that support flexibility and accessibility. Therefore, differentiated instruction is not merely a teaching technique but a foundational component in realizing an equitable, humane, and learner-centered inclusive education system.